Tissue state of anterior abdominal wall in rats after implantation of alloplastic material, processed with collagen, in the abdominal cavity and in contact with hollow organs - Belyanskyi L.S.; Svisenko O.V. (Морфологія, 2010)
A research purpose was to investigate the tissue reactions on implantation of polypropylene mesh, processed withcollagen, after the plastic of experimental defect at rats at intraperitoneal localization of prosthesis in contact with holloworgans. Research was performed in two experimental groups. Group 1 – at 27 rats an experimental defect of of anterior abdominalwall of size 3 cm, with further transabdominal fixation of the polypropylene mesh of size 1×1,5 cm on parietal peritoneumin contact with hollow organs, was performed. Group 2 – at 28 rats at analogous conditions the intraperitoneal fixationof polypropylene mesh, processed with collagen, was performed. Morphological analysis of scar tissue formation phasesin rats in the implantation region in the abdominal cavity and contact with hollow organs from the data of cellular and fiberstructures stereological characteristics of connective tissue with hemodynamic characteristics shows substantial benefits ofuse of polypropylene mesh, processed with collagen, during 4 weeks after experimental hernioplasty.